2005
DOI: 10.1128/aac.49.1.358-365.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Cefoxitin-Resistant Escherichia coli from Canadian Hospitals

Abstract: A study designed to gain baseline information on strains of Escherichia coli displaying resistance to cefoxitin in Canada is described. A total of 29,323 E. coli isolates were screened at 12 participating hospital sites as part of an extended-spectrum beta-lactamase surveillance initiative. A total of 411 clinically significant, nonrepeat isolates displaying reduced susceptibilities to the NCCLS-recommended beta-lactams were submitted to a central laboratory over a 1-year period ending on 30 September 2000. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
100
3
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 32 publications
5
100
3
3
Order By: Relevance
“…5 Whilst we found only three strains with the -42 mutation, other studies have reported a higher prevalence, 13,[17][18][19] with one study finding 100% of isolates with this mutation. 20 Eight of the 40 strains in our study had insertions of either one or two bases at position -13.…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…5 Whilst we found only three strains with the -42 mutation, other studies have reported a higher prevalence, 13,[17][18][19] with one study finding 100% of isolates with this mutation. 20 Eight of the 40 strains in our study had insertions of either one or two bases at position -13.…”
Section: Discussionmentioning
confidence: 38%
“…However, it is not clear whether this has a significant impact on enzyme function. 13 The geometric mean MIC for cefotaxime was 1.2mg/L for all strains, just above the recommended breakpoint of 1.0mg/L. 10 Those strains with the -32 mutation present had a lower cefotaxime MIC of 0.6mg/L, compared to 1.2mg/L for strains with other mutations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have found a higher prevalence for this particular mutation (Mulvey et al 2005;Jorgensen et al 2010;Mammeri et al 2010;Alonso et al 2016), with one reporting a prevalence of 100% (Bogaerts et al 2010). There were two strains (SW-007 and TR-032) that were found to have insertions (thymine) at position -20.…”
mentioning
confidence: 86%
“…Unusually, the -32 mutation (T to A) was the most common (63%); whereas other studies have reported a higher prevalence for the -42 mutation (Mulvey et al 2005;Mammeri et al 2008;Bogaerts et al 2010;Jorgensen et al 2010;Alonso et al 2016). We therefore set out to investigate whether this was also the case in other parts of the South West of England.…”
mentioning
confidence: 95%